Aktivitas Antiinflamasi Ekstrak Etanolik Daun Arbenan [Duchesnea indica (Jacks.) Focke] - Risda Waris; A. Mumtihanah Mursyid (Jurnal Fitofarmaka Indonesia, 2021)
Arbenan leaf is a medicinal plant that used in the healing of inflammation. The content of phenolic compounds, flavonoids, steroids and tannins contained in arbenan plants which play an important role in alternative medicine. Currently, scientific work of phytotherapy is an important alternative route in finding effective natural medicines with minimal side effects. The aim of this study was to determine the phytochemical properties and to determine the anti-inflammatory effect of arbenan leaf [Duchesnea indica (Jacks.) Focke] extract. In this study, nine male Wistar rats were tested in three treatment groups. Group I Na CMC, group II Na diclofenac and group III arbenan leaf extract. Inflammation in rats by inducing 1% carrageenan as much as 0.10 mL. The volume of edema per hour is known from the difference in the volume of the foot at certain hours with the volume of the normal foot. The AUC value of edema volume was calculated by the trapezoid method every one hour and the percen of anti-inflammatory power was calculated. The statistical analysis of the Least Significance Different (LSD) AUC value from the edema volume data showed that the two treatment groups, namely the Na diclofenac and the arbenan leaf extract group, were significantly different from the Na CMC group (P <0.05). So that both treatment groups have anti-inflammatory effects. The results showed that the ethanolik extract of arbenan leaves contained phenolic compounds, flavonoids and tannins. Then the ethanolic extract of arbenan leaves has anti-inflammatory activity of 0.31%.